Efektivitas Pemberian Permen Rasa Mint Terhadap Mual Muntah Pada Post Operasi Sectio Caesaria Dengan Anestesi Spinal Adjuvant Morfin - Edwar Rosady, Ricky; Mixrova Sebayang, Septian; Heri Wibowo, Tophan; Suandika, Made (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Spinal anesthesia with morphine adjuvant can cause post-operative side effects, one of which is nausea and vomiting. Postoperative Nausea and Vomiting (PONV) is a complication that often occurs in anesthesia after 24–48 hours of surgery. Postoperative Nausea and Vomiting (PONV) can be treated with pharmacological and non-pharmacological treatments. Supportive care is provided with pharmacological antiemetics, such as ondansetron, appetite stimulants, and parenteral and enteral nutrition. Management of PONV with non-pharmacological therapies includes aromatherapy, acupressure, distraction, relaxation, and mobilization. The active compounds of peppermint, including menthol and menthone, play a role in its anti-nausea properties. The purpose of this study was to determine the effectiveness of giving mint-flavored perfume on nausea and vomiting in post-Caesarean section surgery with morphine adjuvant spinal anesthesia at Dr. Soekardjo Regional Hospital, Tasikmalaya City. The method in this study is a quantitative pre-experimental type with a One Group Pretest-Posttest research design using a total sampling technique with a sample size of 42 patients. The results of this study are the effectiveness of giving mint-flavored candy to post-Caesarean section patients with Spinal Anesthesia Adjuvant Morphine at Dr. Soekardjo Regional General Hospital, Tasikmalaya City